Analysis of the land administration and housing management systems in view of adequate self-built incremental housing development in Lesotho - Mabesa, Mamphaka Jeanett (School of Architecture, Planning and Geomatics, 2025)
This research analyses the effect of Lesotho's post-reform Land Administration System (LAS) and Housing Management System (HMS) in view of supporting and promoting adequate housing delivery through Self-built Incremental Housing (SBIH) development. SBIH is key to Lesotho's realisation of the Africa Agenda 2063, Sustainable Development Goals (SDGs) 2030 and New Urban Agenda (NUA). This research seeks to provide an integrated and holistic view of SBIH using an approach based on a critical realist ontology. It relies on overarching theoretical and analytic lenses of conflicting rationalities and spatial planning. Ethnographic case study research methodology (ECSRM) is adopted, using a mixed-methods approach. Multiple conflicting rationalities about SBIH development are identified. These are between the central and local governments, governments and LAS and HMS, and the State and the SBIH Dwellers. Looking at the existing land and housing legislative, policy and process frameworks, and their implementation, SBIH continues developing in a fragmented, siloed, conflicting rationality space. Further analysis using the theory of spatial planning provides compelling insights into the LAS and HMS. These include poor policy integration, lack of coordination, and a lack of adaptation of the systems to SBIH Dwellers' needs. Disconnection between these systems and the lived experiences of SBIH Dwellers, particularly their everyday struggles to access adequate housing, remain critical barriers to the success of these systems in meeting the goal of adequate housing through SBIH. The results of this research could guide the design of appropriate SBIH policy and legislative frameworks in Lesotho and feed into State housing delivery processes in line with social needs and SBIH practices and the goal of adequate housing for all. In support of SBIH, this research recommends the integration of the LAS and HMS in Lesotho. All Land Administration and Housing Management aspects should embrace a human-rights-based approach to adequate housing and consider social housing in some form. Furthermore, spatial planning at the local government level should be harmonised with national strategic development plans while capacity development in all arms of the State dealing in this sector, is required. Finally, SBIH guidelines should be produced to mainstream this form of housing delivery. These should include the strategic objectives of SBIH along with performance indicators that seek to address conflicting rationalities and policy disintegration in this space.